設 f(x) = x³ - ax² + bx + 6 , 由因式定理, f(1) = 1 - a + b + 6 = 0 ⇒ a - b = 7 , 只有 B 正確。 f(-2) = - 8 - 4a - 2b + 6 = 0 ⇒ 2a + b = - 1 ⇒ (a+b) + a = - 1 或 2(a+b) - b = - 1 , 兩式相加得 3(a+b) + a - b = - 2 3(a+b) + 7 = - 2 a+b = - 3 , 確定 B 正確。
This entry passed through the Full-Text RSS service - if this is your content and you're reading it on someone else's site, please read the FAQ at fivefilters.org/content-only/faq.php#publishers.
You are receiving this email because you subscribed to this feed at blogtrottr.com.